Photonics and thermodynamics concepts in radiative cooling - Fan, Shanhui; Li, Wei (Nature photonics, 2022)
Radiative cooling is a ubiquitous passive process that uses photon heat flow to carry away energy and entropy. Radiative cooling processes have been studied in the scientific literature for many decades, but advances in nanophotonics have enabled recent breakthroughs in daytime radiative cooling, which have inspired intense research efforts in this area. Radiative cooling is now emerging as a frontier in renewable energy research, with important potential for wide ranges of applications. In this Review, we discuss the fundamental photonics and thermodynamics concepts that underlie the processes of radiative cooling. Understanding of these concepts is essential both for the demonstration of cooling effects and for the development of practical technology. This Review details the fundamental photonics and thermodynamics concepts that underlie the processes of radiative cooling, and discusses a few emerging directions associated with radiative cooling research.